Whole blood sequencing reveals circulating microRNA associations with high-risk traits in non-ST-segment elevation acute coronary syndrome. (June 2017) - Wang, Alice; Kwee, Lydia Coulter; Grass, Elizabeth; Neely, Megan L.; Gregory, Simon G.; Fox, Keith A.A.; Armstrong, Paul W.; White, Harvey D.; Ohman, E. Magnus; Roe, Matthew T.; Shah, Svati H.; Chan, Mark Y.
Abstract: Background and aims: Although circulating microRNA (miRNAs) have emerged as biomarkers predicting mortality in acute coronary syndrome (ACS), more data are needed to understand these mechanisms. Mapping miRNAs to high-risk traits may identify miRNAs involved in pathways conferring risk for poor outcome in ACS. We aim to investigate the relationship between circulating miRNAs and high-risk traits in non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Methods: Whole-genome miRNA sequencing was performed on RNA extracted from whole blood of 199 patients with NSTE-ACS. Generalized linear models were used to test associations of miRNAs and 13 high-risk clinical traits, including the Global Registry of Acute Coronary Events (GRACE) score, a widely validated risk score for mortality in NSTE-ACS. Results: There were 205 nominally significant miRNA-risk factor associations ( p  < 0.05) observed. Significant associations occurred most frequently with chronic heart failure (HF) (43 miRs), GRACE risk score (30 miRs), and renal function (32 miRs). In hierarchical cluster analysis, chronic HF and GRACE risk score clustered most tightly together, sharing 14 miRNAs with matching fold-change direction. Controlling for a false discovery rate of 5%, chronic HF was significantly associated with lower circulating levels of miR-3135b ( p  < 0.0006), miR-126-5p ( p  < 0.0001), miR-142-5p ( p  = 0.0004) and miR-144-5p ( p  = 0.0007), while increasing GRACE risk score inversely correlated with levels of miR-3135b ( p  < 0.0001) and positively correlated with levels of miR-28-3p ( p  = 0.0002). Conclusions: Circulating miRs clustered around two powerful traits for mortality risk in NSTE-ACS. MiR-3135b, which was under-expressed in chronic HF and increasing GRACE risk score, and miR-28-3p, which has no known association with cardiovascular disease, warrant further investigation. Highlights: Whole-genome miRNA sequencing was performed on RNA extracted from patients with non-STE acute coronary syndrome. Circulating miRNAs clustered around chronic heart failure and the GRACE risk score, two powerful traits for mortality risk. Chronic heart failure was significantly associated with lower levels of miR-3135b, miR-126-5p, miR-142-5p and miR-144-5p. Increasing GRACE risk score inversely correlated with levels of miR-3135b and positively correlated with levels of miR-28-3p. Mapping miRNAs to high-risk traits may identify miRNAs involved in pathways conferring risk for poor outcome in ACS.